Nanofiltration and reverse osmosis for defluoridation: The role of inorganic carbon - Schäfer, Andrea Iris; Owusu-Agyeman, Isaac; Jeihanipour, Azam (ECI Digital Archives, 2016)
Fluoride (F) concentrations above the World Health Organization (WHO) guideline value of 1.5 mg/L in drinking water can lead to serious health problems such as dental fluorosis and skeletal fluorosis. High F levels are often associated with carbonaceous (i.e. high inorganic carbon (IC)) type waters. The high fluoride concentrations in natural waters often occur in arid regions where no sufficient quantity of alternative water is readily available due to scarcity of water, consequently, treatment is the best option to provide safe drinking water. Nanofiltration (NF) and reverse osmosis (RO) are promising and appropriate membrane technologies for defluoridation due to their high fluoride removal efficiency and their ability to simultaneously remove a wide range of other inorganic and organic contaminants 1. Different ions can have various effects on F removal by NF/RO 2. IC in natural waters is present as carbonate ion (CO32-), bicarbonate ion (HCO3-), carbonic acid (H2CO3), and carbon dioxide (CO2) depending on the pH. Due to the different characteristics of these species it is important to study the impact of IC on F retention mechanisms at different pH. In this study the mechanisms of IC species impact on F retention by NF/RO has been investigated as a function of pH.Two commercial NF and RO membranes, BW30 and NF270 respectively from DOW Chemicals (USA) were used. Synthetic waters were prepared using realistic ranges of F and IC for carbonaceous waters found for example in the fluoride rich waters in Tanzania. Feed concentration of F and IC were 50 mgF/L as NaF and 500 mgC/L as NaHCO3 respectively. Visual MINTEQ software was used to predict the speciation of IC and F at various pH. Figure 1 indicates that the permeate F concentrations were high (35-47 mg/L) at pH 2 where F existed mainly as uncharged HF. At pH 8 and 11, when there was a change in speciation to F ion and the membranes were negatively charged, permeate F concentrations decreased drastically. Permeate F concentrations for the RO BW30 membrane ...